2019
DOI: 10.3390/antiox8080265
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Oxidative/Nitrosative Stress Contributes to Parkinson’s Disease Pathogenesis: The Dual Role of Reactive Astrocytes

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease worldwide; it is characterized by dopaminergic neurodegeneration in the substantia nigra pars compacta, but its etiology is not fully understood. Astrocytes, a class of glial cells in the central nervous system (CNS), provide critical structural and metabolic support to neurons, but growing evidence reveals that astrocytic oxidative and nitrosative stress contributes to PD pathogenesis. As astrocytes play a critical role in the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 155 publications
(175 reference statements)
4
55
0
Order By: Relevance
“…Clearly, various interactions between exogenous tVM-As and the pathological host milieu may underlie the improvement herein observed, and further time-course studies and in-depth molecular analyses both at a tissue and at a single-cell level are clearly needed to unravel how tVM-As grafts may drive a DAergic neurorescue program. However, from the presented results and based on our previous (see L 'Episcopo et al, 2012'Episcopo et al, , 2013'Episcopo et al, , 2014b'Episcopo et al, , 2018a and as reviewed by Marchetti, 2018) and the recent literature findings (Tebay et al, 2015;Zhang et al, 2015Zhang et al, , 2017Zheng et al, 2017;Rizor et al, 2019), it seems tempting to speculate that the observed changes might result from a beneficial tVM-As-to-host SN crosstalk, promoting the rejuvenation of the host microenvironment, through the activation of an astrocytic Nrf2/ARE/Wnt/β-catenin prosurvival axis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Clearly, various interactions between exogenous tVM-As and the pathological host milieu may underlie the improvement herein observed, and further time-course studies and in-depth molecular analyses both at a tissue and at a single-cell level are clearly needed to unravel how tVM-As grafts may drive a DAergic neurorescue program. However, from the presented results and based on our previous (see L 'Episcopo et al, 2012'Episcopo et al, , 2013'Episcopo et al, , 2014b'Episcopo et al, , 2018a and as reviewed by Marchetti, 2018) and the recent literature findings (Tebay et al, 2015;Zhang et al, 2015Zhang et al, , 2017Zheng et al, 2017;Rizor et al, 2019), it seems tempting to speculate that the observed changes might result from a beneficial tVM-As-to-host SN crosstalk, promoting the rejuvenation of the host microenvironment, through the activation of an astrocytic Nrf2/ARE/Wnt/β-catenin prosurvival axis.…”
Section: Discussionsupporting
confidence: 54%
“…Remarkably, previous studies of Chen et al (2009) indicated that Nrf2 expression restricted to As is sufficient to protect against MPTP toxicity, suggesting that As modulation of the Nrf2-ARE pathway is a promising target for therapeutics aimed at reducing or preventing neuronal death in PD (Chen et al, 2009). Significantly, Lastres-Becker et al (2012) reported that α-synuclein expression and Nrf2 deficiency cooperate to aggravate protein aggregation, neuronal death, and inflammation in early-stage PD, and very recent findings further define As oxidative/nitrosative stress as a key etiopathogenetic factor in PD (Rizor et al, 2019). Additionally, we pinpointed that by middle age, a significant decrease of Nrf2/HO1 response to MPTP in striatal and SVZ-As played a prominent role and synergized with the heightened inflammatory SVZ milieu to downregulate SVZ neurogenesis (L'Episcopo et al, 2013).…”
Section: As Grafting Switched the Harmful Sn Milieu Of Aging Mptp Micmentioning
confidence: 97%
“…The role of astrocytes as antioxidant supporters for neurons is well accepted [106][107][108], and the loss of this support was often shown to lead to neuronal death in diverse neurodegenerative diseases [109,110]. Oxidative stress, associated with the activation of both mitochondrial and endoplasmic reticulum (ER) stress responses in astrocytes, was indeed shown to be involved in the pathophysiology of distinct ataxias (Figure 2).…”
Section: When Astrocytes "Burn Out": Stressed Astrocytes Cause Accumumentioning
confidence: 98%
“…Oxidative stress and mitochondrial dysfunction play an important role in exacerbating PD [143][144][145][146]. Indeed, cellular in lammation and stress are known to cause reactive astrogliosis, which in turn leads to the generation of astrocytic ROS [147]. In this context, ROS are regarded as important modulators of PD [148,149].…”
Section: Parkinson's Disease and Oxidative Stressmentioning
confidence: 99%